Hermite polynomials linking Szász–Durrmeyer operators - Ayman-Mursaleen, Mohammad; Heshamuddin, Md; Rao, Nadeem; Sinha, Brijesh Kumar; Yadav, Avinash Kumar (Computational & applied mathematics, 2024)
The aim of present article is to introduce the Szász-integral type sequences of operators in terms of Hermite polynomials and gamma function. Further, we calculate some estimates at test functions and central moments. Moreover, we discuss uniform convergence theorem and order of approximation via Korovkin theorem and first order modulus of smoothness respectively. Next, we study pointwise approximation results in view of Peetre’s K -functional, second order modulus of smoothness and Lipschitz type space. Lastly, bivariate version of these sequences of operators are introduced. Moreover, their rate of convergence and order of approximation are investigated.